Answer:
2Step-by-step explanation:
Given function
f(x)=x⁴−x³−2x−4Factoring the polynomial
x⁴−x³−2x−4 = (x⁴−4) − (x³+2x) =(x² + 2)(x² - 2) - x(x² + 2) =(x² + 2)(x² - x - 2) =(x + i√2)(x - i√2)(x - 2)(x + 1)As we see there are 2 complex factors
Answer:
(x+1)(x-2)(x+i√2)(x-i√2)
Step-by-step explanation:
y = x +13 solve for y if x = 5
Step-by-step explanation:
y = x+13
If x = 5
Then,
y = 5 + 13
y = 18
Hence,
The value of y is 18.
Answer:
y=18
Step-by-step explanation:
y=(5)+13
5+13=18
y=18
What is y-6 = 2(x + 5) in standard form?
A. -2x + y= 16
B. 2x-y=-16
C. y= 2x + 16
D. y-6 = 2x + 10
Answer:
Your answer is A
Step-by-step explanation:
Mrs. Oliver has a stick that is 5 feet 8 inches. How many inches long is the stick?
Answer: sorry read it wrong
Answer:
68 inches
Step-by-step explanation:
We know that a foot is 12 inches, so multiply 12 and 5 to get 60, and then add the 8 other inches.
I hope this helps, and if it does, may I have brainliest?
Insert <, >, or = between the quantities to make a true comparison.
(23-9)+(6+1) 23-9+6+1
a. <
b. >
C.=
Answer:
c
Step-by-step explanation:
It’s the same thing even if you put ()
What is the equation for the line of reflection?
38,956 rounded to the nearest 10,000
Answer:
40,000
Step-by-step explanation:
38,956 rounded to the nearest 10,000 is 40,000
Answer: 39,000
Step-by-step explanation:
What should be done to both sides of the equation in order to solve -5m = -40?
Divide by -5.
Divide by -40.
Multiply by -5.
Multiply by -40
Answer:
Divide by -5.
h(t)= 50-t/5
h(35) =
Answer:
125
Step-by-step explanation:
Answer:
h= 50 - th(35)/5
Step-by-step explanation:
cos(t) = 4/5
What is the value of t?
Answer:
t = 0.6435 in radians or 36.8699 in degrees
Step-by-step explanation:
Since cos(t) = 4/5, t = inverse cos(4/5) = 0.6435
10 pounds of flour cost $8. How much does 40 pounds of flour cost? What is the cost per pound of flour?
Answer: 1.25
Find my question since I had this question and look at the answer ok
Step-by-step explanation:
I hope my answer helps you out have a great day
I need the value of x
Answer:
9.9
Step-by-step explanation:
Optional (extra) info to understand length of other leg:
This triangle is an iscoceles, how can I (or we) tell?? Well, the angles of a triangle always add up to 180° and we know the angles of 2 corners, 90° and 45° so we can do this to find the last angle where "c" is the unknown corner:
180 - (90 + 45) = c
180 - 135 = c
45 = c
so "c" is also equal to 45° so we can decisively conclude that this figure is an iscoceles triangle.
How to find x:
Use the pythagorean theorem
c = √a² + b²
Then calculate using that equation
c = √7² + 7²
c = 9.9
In this case "c" is for the length of hypotenus but the image asks for x so
x = c
and
c = 9.9
so
x = 9.9
Hope this helps!
Have a nice evening!
If you find my answer helpful
Pls consider marking my answer as Brainliest! It would mean a lot!
Answer:
it x = 9.9
Step-by-step explanation:
Tabetha spends $1.79 on a 20 oz bottle of Mountain Dew. How much did she pay per ounce?
Answer:9 cents per ounce (0.0895)
Step-by-step explanation: I UNDERSTAND HOW FRUSTRATING IT IS TO PUT AN ANSWER AND NO ONE ANSWERS IT, I DO, SO ALL I ASK IS FOR YOU TO GIVE ME BRAINLIEST. THANK YOU.
HELP PLEASE IM GOING TO FAIL MATH :(
Answer:
r=11, Hope I helped!
Step-by-step explanation:
I'm to lazy :P
Answer:
r=11
Step-by-step explanation:
Notice on the table how whatever the x value you is it is multiplied by 11, thus giving us our answer to r and answer to the equation y = rx.
what is 12% of $5000 for 3yrs
Answer:
$7,025
Step-by-step explanation:
1. Let S(x) represents a faculty member's yearly salary x years after beginning a position at a university. a. Use function notation to represent $2300 more than a faculty member's salary after 6 years on the job. b. Use function notation to represent the salary of a faculty member after 3 years more than n years on the job. c. Use function notation to represent a salary that is 2 times as large as the salary of a faculty member after 5 years on the job. d. How many times as large is the salary of a faculty member who has been on the job for 14 years as compared to someone who has been on the job for 3.1 years?
Answer:
a)S(6)+2300
b)S(n+3)
c)2(S(5))
d)S(14)-S(3.1) more than salary of member who has been on the job for 14 years as compared to someone who has been on the job for 3.1 years
Step-by-step explanation:
Let S(x) represents a faculty member's yearly salary x years after beginning a position at a university.
a)Use function notation to represent $2300 more than a faculty member's salary after 6 years on the job
$2300 more than a faculty member's salary after 6 years on the job : S(6)+2300
b)Use function notation to represent the salary of a faculty member after 3 years more than n years on the job.
The salary of a faculty member after 3 years more than n years on the job : S(n+3)
c)Use function notation to represent a salary that is 2 times as large as the salary of a faculty member after 5 years on the job.
A salary that is 2 times as large as the salary of a faculty member after 5 years on the job :
2(S(5))
d)How many times as large is the salary of a faculty member who has been on the job for 14 years as compared to someone who has been on the job for 3.1 years?
S(14)=S(3.1)
S(14)-S(3.1) more than salary of member who has been on the job for 14 years as compared to someone who has been on the job for 3.1 years
The function notations for the given question are:
a. [tex]\rm S(x)=S(6)[/tex]
b. [tex]\rm S(x) = S(n+3)[/tex]
c. [tex]\rm S(x) = 2[S(5)][/tex]
d. [tex]\rm S(x) = S(14) - S(3.1)[/tex]
What is Function Notations?Function notations can be defined as a method of writing functions that are precise and easy to understand. Function notations is a way to convert lengthy texts into functions. The most commonly used functional notation is f(x).
For the given question, let S(x) be the salary of a faculty member after x years.
a.The functional notation to represent a faculty member's salary after 6 years is:
[tex]\rm S(x)=S(6)[/tex] , where 6 is the number of years and S is the salary per year.
b. The functional notation to represent salary of a faculty member after 3 years more than n years on the job is:
[tex]\rm S(x) = S(n+3)[/tex] , where n+3 represents number of years into the job.
c. The functional notation to represent a salary that is 2 times as large as the salary of a faculty member after 5 years on the job is:
[tex]\rm S(x) = 2[S(5)][/tex] , where S(5) is the salary after 5 years into the job.
d. The difference between salary of a faculty member after 14 years and salary of another faculty member after 3.1 years can be represented as:
[tex]\rm S(x) = S(14) - S(3.1)[/tex], where S(14) is the salary after 14 years and S(3.1) is the salary after 3.1 years into the job.
Therefore the functional notations for the given question are:
a. [tex]\rm S(x)=S(6)[/tex]
b. [tex]\rm S(x) = S(n+3)[/tex]
c. [tex]\rm S(x) = 2[S(5)][/tex]
d. [tex]\rm S(x) = S(14) - S(3.1)[/tex]
Learn more about function notations here:
https://brainly.com/question/5025688
A yard stick is about how wide?
Answer:
3 feet long about 1 1\2 inch wide though
Step-by-step explanation:
.
3 feet
36 inches
0.000568182 of a mile
Long
please help put the solution only if you can. thank you!
========================================================
Explanation:
Highlight XY in the sequence XYZ. We've highlighted the first two letters.
This means that we'll need to highlight the first two letters of MNL to get MN.
XY pairs with its corresponding part MN.
Due to the congruent triangles, we know that XY = MN.
The diagram shows MN = 8. Due to substitution or the transitive property (they're similar ideas) we know that XY = 8 as well.
As you can see, the order of the letters is important so we can properly align the letters.
-2(7-15)
What is the value of
O 2
Please I need help
The answer to this is 16
A right triangle has side lengths
Answer:
tan b
Step-by-step explanation:
I need help PLEASE!!!!
Step-by-step explanation:
Hope I am not wrong! I did my best I could!
Sorry for the mistakes and my bad writing!
What is X? 3(-x-3)+x-3=-24
Answer:
x is equal to 6
Step-by-step explanation:
Hey there!
3(-x-3) + x-3= -24
Multiply"3" and (-x-3).
-3x - 9 + x - 3 = -24
Add or subtract like terms.
-2x - 12 = -24
Shift "-12" in right side.
-2x = -24+12
-2x = -12
Divide "-12" by "-2".
X = -12/-2
Therefore, x= 6.
Hope it helps...
6th grade math i mark as brainleist or whatever thats spelled
A country's postal service will accept a package if its length plus its girth (the distance all the way around) does not exceed 96 inches. Find the dimensions and volume of the largest package with a square base that can be mailed. length in base in × in volume in3
Answer:
Following are the solution to the given point:
Step-by-step explanation:
Let the box length l and the square base side be x, then
[tex]\to l+4x= 96 \\\\\to l=96-4x[/tex]
Calculating the volume of the box is:
[tex]\to V (x) = x^2 \\\\ \to l = x^2(96-4x)[/tex]
To find the critical value in this way, distinguish V with x and equal to zero
[tex]\to V'(x)=0 \\\\\to 4 \frac{d}{dx}(24x^2 - x^3)=0\\\\\to 4 (48x- 3x^2)=0\\\\\to 12x(16-x) = 0\\\\\to x= 12... [x \neq 0][/tex] (because the box will not exists)
Find the second derivative for maximum / minimum control as:
[tex]\to V''(x)= 12 \frac{d}{dx} (16x-x^2) \\\\\to 12 (16 -2x) < 0 \ for \ x = 16 \to \ Maxima \\\\\therefore[/tex]
[tex]Length = 32 \\\\Base = 16 in \times 16 in \\\\Volume= 8,192 \ in^3[/tex]
Add the Polynomials
(7-7p4) + (5p4 + 7)
Solve the equation.
3x + 2(4x - 6) = 8x + 1
What is the value for x?
w
Answer:
=
1
3
3
Step-by-step explanation:
19-6x=-11
what is x?
Answer:
x = 5
Step-by-step explanation:
19 - 6x = -11
-6x= -11 -19
-6x = -30
x= 5
Answer:
x = 5
Step-by-step explanation:
19 - 6x = -11
-6x = -11 - 19
-6x = -30
-6x/-6 = -30/-6
x = 5
19 - 6*5 = -11
19 - 30 = -11
-11 = -11
help me i'm gonna fail!!!!!!!
Answer:
ok give me brainliest and i'll help
Step-by-step explanation:
Answer:
what is it that u need help with?
g A person who is 6 feet tall is walking away from a lamp post at the rate of 40 feet per minute. When the person is 10 feet from the lamp post, his shadow is 20 feet long. Find the rate at which the length of the shadow is increasing when he is 30 feet from the lamp post.
Answer:
80 ft/min
Step-by-step explanation:
Let h represent the height of the person shadow, x represent the distance between the person and the lamppost, y represent the length of the man shadow.
Therefore:
[tex]\frac{h}{x+y} =\frac{6}{y} \\\\substituting\ x=10,y=20:\\\\\frac{h}{10+20} =\frac{6}{20}\\\\\frac{h}{30} =\frac{6}{20}\\\\h=30*6/20\\\\h=9\ feet\\\\Therefore:\\\frac{h}{x+y} =\frac{6}{y}\\\\\frac{9}{x+y} =\frac{6}{y}\\\\9y=6x+6y\\\\9y-6y=6x\\\\3y=6x\\\\y=2x\\\\The\ person\ is\ walking\ from\ the\ lamppost\ at\ 40ft/min(\frac{dx}{dt}=40\ ft/min) \\\\y=2x\\\\Differentiating\ with\ respect\ to\ t:\\\\\frac{dy}{dt} =\frac{d}{dt}(2x)\\\\\frac{dy}{dt} =2\frac{dx}{dt}\\\\[/tex]
[tex]\frac{dy}{dt} =2(40\ ft/min)\\\\\frac{dy}{dt}=80\ ft/min[/tex]
The rate at which the length of the shadow is increasing when he is 30 feet away from the lamp post is 80 [tex]\frac{ft}{min}[/tex].
The height of the person shadow is to be = h
Given ,
The distance between the person and the man = x = 10
The length of the man shadow is = y = 20
By the similar triangle property corresponding sides of similar triangles are in the same ratio.
[tex]\frac{h}{x+y} = \frac{6}{y}[/tex]
[tex]\frac{h}{10+20} = \frac{6}{20}[/tex]
20h = 60 + 120
20h = 180
h = [tex]\frac{180}{20}[/tex]
h = 9feet
Therefore,
[tex]\frac{h}{x+y} = \frac{6}{y} \\\frac{9}{x+y} = \frac{6}{y} \\[/tex]
9y= 6x + 6y
9y-6y = 6x
6x = 3y
y = [tex]\frac{6}{3}x[/tex]
y = 2x
Differentiating both the sides with respect t,
[tex]\frac{dy}{dt} = 2\frac{dx}{dt}[/tex]
we know that ;
[tex]\frac{dx}{dt} = 40 \frac{ft}{sec}[/tex]
Therefore, by substitute the value
[tex]\frac{dy}{dt} = 2 . 40\frac{ft}{min}[/tex]
[tex]\frac{dy}{dt}[/tex] = 80[tex]\frac{ft}{min}[/tex].
The rate at which the length of the shadow is increasing is 80[tex]\frac{ft}{min}[/tex] .
For more details about the Rate change problem click the link given below.
https://brainly.com/question/20414862
describe and solve the error 3x - 5 + 2x² + 9x = 3x + 2x² + 9x - 5
Answer:
3x - 5 + 2x² + 9x = 3x + 2x² + 9x - 5 = TRUE = 2 x^2 + 12 x - 5
Step-by-step explanation:
left: Simplify the following:
2 x^2 + 9 x + 3 x - 5
Grouping like terms, 2 x^2 + 9 x + 3 x - 5 = 2 x^2 + (3 x + 9 x) - 5:
2 x^2 + (3 x + 9 x) - 5
3 x + 9 x = 12 x:
Answer: 2 x^2 + 12 x - 5
_______________________
Simplify the following:
2 x^2 + 9 x + 3 x - 5
Grouping like terms, 2 x^2 + 9 x + 3 x - 5 = 2 x^2 + (3 x + 9 x) - 5:
2 x^2 + (3 x + 9 x) - 5
3 x + 9 x = 12 x:
Answer: 2 x^2 + 12 x - 5
which equation represents exponential decay
Answer:
You have to show the question
Step-by-step explanation: